PERANCANGAN DOKUMEN HAZARD IDENTIFICATION, RISK ASSESSMENT, AND RISK CONTROL (HIRARC) DI CV PENJUNAN SEJAHTERA - Chedie Putra Hardiyanto; Kriswanto Widiawan (Jurnal Titra, 2021)
CV Penjunan Sejahtera is a company engaged in the service sector. Based on the results of interviews with company owners, it was found that there have been work accidents several times since the company's inception until now. Document design using the HIRARC method aims to assist CV Penjunan Sejahtera in identifying various work activities that have potential hazards, by providing a risk assessment of these potential hazards, as well as providing suggestions for improving risk control. The results of the design of the HIRARC document indicate that there are still many potentially hazardous work activities at each existing workstation. The activities include an activity with a low risk level of one event, a moderate risk level of 15 events, and a significant risk level of 19 events. Then the risk control stage will be carried out which aims to minimize the risk of potential hazards in five ways, namely elimination, substitution, technical engineering, administrative, and Personal Protective Equipment (PPE). The risk rating reduction forecast is an estimate, if the risk control that has been proposed by the researcher is carried out by the company, then the reduction in the risk level which was initially quite dangerous becomes significantly reduced.